Host and environmental determinants of in-hospital mortality in community-acquired pneumonia: evidence of seasonality, socioeconomic factors, and hospital differentiation in Portugal - Ezequiel Pessoa; Cristina Bárbara; Andreia Costa; Paulo Nogueira (BMC Pulmonary Medicine)
Abstract Background Community-Acquired Pneumonia (CAP) is regarded as a substantial part of the global burden of disease and a public health priority. In addition to host factors, such as demographic characteristics, comorbidities, CAP clinical severity, and in-hospital mortality may also be influenced by factors such as socioeconomic status, seasonal variations, and hospital differentiation. This study aims to analyse trends in hospital mortality among patients hospitalized with CAP in National Health Service (NHS) hospitals in mainland Portugal and the impact of various host and environmental factors on in-hospital mortality.  Methods This retrospective cross-sectional study analyzed 378,449 hospitalization episodes with CAP as the primary diagnosis (ICD-9-CM and ICD-10-CM/PCS) in mainland Portugal from 2010 to 2018. Data were sourced from the National Hospital Discharge Database and population census records. Variables included host factors (demographic characteristics, secondary diagnoses, CAP clinical severity indicators, Charlson score) as well as environmental factors, such as seasonality, socioeconomic factors and hospital differentiation. Trend analysis of hospitalization episodes and in-hospital mortality due to CAP was performed. Multivariable logistic regression was used to examine associations with in-hospital mortality, with statistical significance set at p < 0.05. Results A decrease in the number of hospitalization episodes and in-hospital mortality rate over time was observed. The regression model identified advanced age, male gender, secondary diagnoses, CAP clinical severity, high Charlson score, the summer season, early school leaving rate, higher unemployment rate, and lower hospital differentiation as factors associated with an increased probability of death (p < 0.001).  Conclusions Throughout the nine-year period, a steady decline in in-hospital mortality rates was observed. In-hospital mortality exhibited a dual influence, shaped by host factors (such as age, gender, secondary diagnoses, CAP clinical severity, Charlson score) and environmental factors, including the summer season, socioeconomic vulnerability and hospital capabilities. Therefore, effectively reducing CAP in-hospital mortality requires comprehensive policies that focus on at-risk groups and address a broad range of both host and environmental risk factors. These policies should aim to improve healthcare access, increase vaccination coverage, and enhance thermal housing conditions, with particular attention to socially vulnerable individuals.